DELEGITIMATION OF STATE POWER IN THE FACTORIAL DIMENSION - Олейников, Сергій (SWorldJournal, 2025)
The article describes the phenomenon of the crisis of legitimacy of power as a complex process within society and law with politics that affects the state and society. The main significant factors of delegitimization of state power are identified: social